2022
DOI: 10.26444/aaem/155307
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prevalence of potentially infectious enteric viruses in surface waters below treated wastewater discharge

Abstract: Stobnicka-Kupiec A, Górny RL. Seasonal prevalence of potentially infectious enteric viruses in the surface waters below treated wastewater discharge. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…These results are in line with what was found in the study by Stobnicka-Kupiec&Górny [28] where the prevalence of positive rotavirus samples found in winter (dry period) was higher than those found in summer (rainy period) (73.3% vs. 26.7%), with there also being an statistics association between the prevalence and the period found (x2: p = 0.028; Fisherʹs Exact test: p = 0.033). Different from what was found in our study, in a study in the State of Minas Gerais, where there is also a higher incidence of rotavirus during the dry period, the RVA were found in water samples collected on both dry (54.1 %=13/24) and rainy period (70.8 %=17/24) but no significant association between the viral detection and the period in which the study was realized were found(p=0.371) [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with what was found in the study by Stobnicka-Kupiec&Górny [28] where the prevalence of positive rotavirus samples found in winter (dry period) was higher than those found in summer (rainy period) (73.3% vs. 26.7%), with there also being an statistics association between the prevalence and the period found (x2: p = 0.028; Fisherʹs Exact test: p = 0.033). Different from what was found in our study, in a study in the State of Minas Gerais, where there is also a higher incidence of rotavirus during the dry period, the RVA were found in water samples collected on both dry (54.1 %=13/24) and rainy period (70.8 %=17/24) but no significant association between the viral detection and the period in which the study was realized were found(p=0.371) [21].…”
Section: Discussionsupporting
confidence: 92%
“…Outbreaks of infection not reported in the study areas, the elimination of feces with high concentrations of the virus (which can reach 10 8 to 10 11 particles/gram of feces) by infected patients, in addition to characteristics specific to the virus, may explain its greater detection of RV in the samples [9,10,16,20]. RVs survive diverse conditions and are capable of surviving for long periods, contributing to their prevalence in the environment [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation